History Learning Through Multicultural Approach as Strategy for Peace Education - Sariyatun, Renny Pujiartati & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
A historical reality in the reform era right now, on one side of the nation of Indonesia hasthe hope of a brighter future. On the other hand, the people of Indonesia entered the multidimensionalcrisis accompanied by separatist movements and socio-cultural issues ofconcerns regarding riot and disintegration of the nation. To overcome these problems,required education instilling the principles of peace to learners. Learning history played animportant role in internalization and build awareness of multiculturalism to learners. In theevent there is a history of values that can be used to develop the hard skills and soft skills.Through internalization of multicultural values, for example the values of peace, harmony,complexity of reality sosio-historis and unity in the process of learning history can broadenthe horizon of thinking learners.Keyword: History Learning, Multicultural Approach, Peace Education